O ensino médio noturno no município de Realeza –PR: análise sobre a relação escola, trabalho e juventude - Machado, João Victor (2023)
This master's thesis is part of the Society, Knowledge, and Education Research Line of the Postgraduate Program in Education (PPGE) of the State University of Western Paraná (Unioeste), Francisco Beltrão campus - PR. The main objective was to analyze the relationship between youth, school, and work, considering the school experiences of young people in evening secondary school in the municipality of Realeza -PR. To this end, the methodological approach adopted was Historical and Dialectical Materialism, and the research was carried out using a qualitative approach, with semi-structured interviews applied to 24 third-year evening secondary school students at School Doze de Novembro, in the municipality in question. The interviews aimed to understand and present the profile of the young people who attend night school in Realeza - PR, as well as to analyze their experiences concerning work, school, and youth. Through the information gathered and the interviews conducted, we also tried to show how the relationships between these young people and the school develop, mediated by their work relationships. The research also explored, albeit briefly, the categories and concepts needed to understand the aspects that encompass this relationship, such as work, a category analyzed from Marx's perspective, with contributions from Harvey (2008) and Antunes (2018), Education and the school context are also discussed, based on Saviani (1996) and Kuenzer (1989), in addition to addressing the understanding of youth and the plurality that the concept encompasses, using the works of Dayrell (2003) and Groppo (2017). A historical overview of evening education in Brazil and its characteristics is also presented, based on Oliveira (2011), Romanelli (1986), Aranha (1996), and other theorists who help to understand the construction of evening education as it currently stands, permeated by neoliberal interests. Thus, in addition to drawing up a profile of evening school students in Realeza - PR, this research has made it possible to understand how these individuals' lives are crossed by the need to work and to enter the job market, demonstrating their relationship with the school. In addition, it was possible to understand the complexity of the reality of evening school, the multiplicity of experiences that make up this level of education, broadening the view of the multiple determinants that make up the whole of this reality, such as the relationship with work and its implications and nuances for the living conditions of young people in the working class.